2013
DOI: 10.1267/ahc.12030
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Situ</i> Hybridization Method Reveals (Pro)renin Receptor Expressing Cells in the Pituitary Gland of Rats: Correlation with Anterior Pituitary Hormones

Abstract: Expression of (pro)renin receptor ((P)RR), a specific receptor for renin and prorenin, was studied in rat pituitary gland. In situ hybridization showed that cells expressing (P)RR mRNA were widely distributed in the anterior lobe and intermediate lobe of the pituitary gland. Double-staining using in situ hybridization for (P)RR mRNA and immunohistochemistry for the pituitary hormones showed that (P)RR mRNA was expressed in most of the GH cells and ACTH cells in the anterior lobe. (P)RR mRNA was also expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…(P)RR is expressed in various types of cells, including neurons, endocrine cells, lymphocytes, cardiomyocytes, and renal tubular cells (Hirose et al 2009;Takahashi et al 2010aTakahashi et al , 2010bTakahashi et al , 2013Narumi et al 2015). We have previously reported expression of (P)RR in a human erythroblastic cell line, YN-1 and its clonal variant cell line, YN-1-0-A (Kaneko et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…(P)RR is expressed in various types of cells, including neurons, endocrine cells, lymphocytes, cardiomyocytes, and renal tubular cells (Hirose et al 2009;Takahashi et al 2010aTakahashi et al , 2010bTakahashi et al , 2013Narumi et al 2015). We have previously reported expression of (P)RR in a human erythroblastic cell line, YN-1 and its clonal variant cell line, YN-1-0-A (Kaneko et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the effect of bafilomycin A1 on the cell growth inhibition and apoptosis was remarkably enhanced by hirsutanol A in MCF-7 breast carcinoma cells (34). (P)RR was widely expressed in various types of cells and tissues including brain, kidney, adrenal and adrenal tumors, and certain cultured tumor cells (7,8,11,20,(29)(30)(31)33). However, there has been no report on expression of (P)RR in breast carcinoma tissues.…”
mentioning
confidence: 99%
“…Interestingly, AVP and oxytocin are shown to co-localize with (P)RR in the supraoptic and paraventricular nuclei in human and mouse hypothalamus [ 74 , 75 ]. Furthermore, a recent study using in situ hybridization for (P)RR mRNA and immunohistochemistry double-staining for the pituitary hormones showed that (P)RR mRNA was expressed in most of the GH cells and ACTH cells in the anterior lobe of the pituitary gland, strongly suggesting a central crosstalk between AVP release and (P)RR, but further investigation on this issue is demanded [ 76 ].…”
Section: Discussionmentioning
confidence: 99%